Comparative Analysis of Punctuation Use in Scientific and Academic Styles: English and Uzbek Languages (American Scholar: Journal of Interdisciplinary Research and Knowledge, 2026)
This article examines the functional and stylistic use of punctuation marks in scientific and academic discourse in English and Uzbek. The study focuses on how punctuation contributes to logical structuring, coherence, and epistemic clarity in two typologically different languages. The analysis reveals both universal tendencies (logical segmentation, syntactic precision) and language-specific conventions shaped by orthographic traditions and academic writing norms. The research is grounded in comparative linguistics and discourse analysis frameworks.
Keywords: punctuation; academic style; scientific discourse